VALIDITY OF THE THESIS JOCKEY SERVICES AGREEMENT - Fathurrahman , M. Aditya; Mediawati, Noor Fatimah (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
General Background: The increasing demand for academic support services has led to the emergence of thesis jockey services, raising important legal questions regarding the validity of such agreements. Specific Background: This research specifically examines the legal conditions necessary for the validity of thesis jockey service agreements, focusing on their compliance with the Civil Code. Knowledge Gap: Despite the growing prevalence of these services, there is limited scholarly analysis on the legal implications and protections surrounding them. Aims: The study aims to explore the validity of thesis jockey service agreements by assessing their halal causes in relation to thesis consultation services. Results: Utilizing a normative juridical methodology with a statutory approach, the findings reveal that the validity of these agreements hinges on specific criteria outlined in the Civil Code, particularly concerning lawful objectives and mutual consent. Novelty: This research contributes to the discourse by highlighting the often-overlooked legal implications of thesis jockey services and the necessity for clarity in their contractual frameworks. Implications: The findings underscore the importance of legal awareness among stakeholders and advocate for enhanced protections to ensure the validity of thesis jockey service agreements, thereby promoting ethical academic practices and safeguarding the interests of all parties involved.